Forage garden for encouraging potential fodder crops - Chand, Subhash; Roy, Ajoy Kumar; Yadav, Vijay Kumar; Agrawal, Rajiv Kumar (Indian Farming, 2024)
Livestock farming is a vital component of the rural based economy in India and provides livelihood to two-third of the rural community. India has large diversity in livestock and also provides employment to nearly 8.8% of the total population. Increasing health awareness, urbanization and socio-economic status will lead to more demand for food from livestock. Low livestock productivity and increased product prices are mainly due to insufficient availability of nutritious green and dry fodder round the year across the country. Fodder crops offer cost-effective, eco-friendly, resource efficient and sustainable sources to maintain livestock productivity and vigour in the long term. Nevertheless, the country is facing an 11.24% shortage in green fodder and 23.4% in dry matter, therefore fodder crops with high biomass and nutritional superiority can be the best choice for the livestock keepers. All India Coordinated Research Project on Forage Crops and Utilization has established more than 50 forage gardens across the country for sensitizing fodder crops and their high yielding varieties including annuals and perennials, and more awareness among farmers and livestock keepers.